Micellization of TPGS-1000: understanding the thermodynamics and related solute-solvent interactions using conductometric technique / Hadiatul Ain Hasanuddin - Hasanuddin, Hadiatul Ain (2014)
TPGS-1000 has been shown to have wide array of potentials in the field of pharmaceutical sciences. The present study involves the determination of the critical rnicelle concentration (CMC) of TPGS-1000 in water so to revalidate the value from literature. The conductometric technique has been used for the determination of the CMC value. The obtained value is well agreed with that of the literature. The temperature dependence of the CMC in case ofTPGS-1000 has been observed to be negligible. Further the observed specific conductance values during conductometric measurements have been used to evaluate the corresponding values of molar conductance. The values of activation energy related to the different concentrations of TPGS-1000 have been estimated using the Arrhenius equation. The thermodynamic parameters for the rnicellization process of TPGS-1000 in water have also been calculated.